مدى معرفة المرأة بمعلومات البطاقة الارشادیة المرفقة بالملابس والمفروشات في مدینة بغداد - أ. ھالة الخیري (College of Education for Women, 2019)
It takes a long time and a lot of money to choose and provide clothes. It is soothing necessary to care of them in order to use it another time. There is no Disposable clothes until now, like other things in the house which we used for once then we dropped, then we can use new one without any time or effort can be mentioned like needles, nappy, tissues and etc. The clothes are different; people should take care of and clean them again in order to use them again. The right care of clothes would make them last for a long time. So, there is no need to buy a new one instead of them in a short time. This thing provides time and effort for the people and the family, to affect positively on the family's budget. We should use to care for the clothes by following the right and suitable means, because there are many clothes have very easy ways to deal with them successfully at home in order to look elegance and acceptable. This is something very important to those who are specialists at home economics directly towards the family. For inferring the extent of women's knowledge of the instructional label information that comes with the clothes and furniture in Baghdad, the researcher has performed a test (a subjective one) consisting of ( 30 ) items and distributed them to ( 4 ) axis's which involve primary information that every woman should learn. The test has been applied on ( 100 ) responders and proved that such knowledge is of a low level especially in a plain symbolic axis. Eventually, the researcher has presented some suggestions and recommendations.